2020
DOI: 10.22271/chemi.2020.v8.i2ai.9097
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficacy of some physico-chemical and hormonal treatments for dormancy removal & germination improvement in Bunium persicum (Kala Zeera)

Abstract: The aim of this study was to determine the efficacy of some physico-chemical and hormonal treatments for dormancy removal / germination improvement. In laboratory experiment, seeds were subjected to various hormonal treatments like Gibberellic acid (0.01mM & 0.1mM), Indole Acetic acid (.01mM & 0.1mM) & Kinetin (0.01mM & 0.1 mM) for 24h. Seeds were also subjected to 24h, 48h running water for leaching and seed were kept for moist chilling at 4 0 C for 2 months. Seeds were also treated with hormones (48h L +Kn (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Since GA 3 and cold stratification increased seed germination, the seeds also have PD (Figures 4 and 5), i.e., they have MPD. Our data are in parallel with the previous results of Sharifi and Pouresmael (2006) and Banyal and Sharma (2020), who reported MPD for B. persicum seeds, but different from those of Sharma and Sharma (2010) and Saeidnejad et al (2013), who reported only PD. However, none of these four studies provided any information on the embryo growth prior to germination, and hence the seed dormancy class was only determined based on seed germination responses to cold stratification and GA 3 treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Since GA 3 and cold stratification increased seed germination, the seeds also have PD (Figures 4 and 5), i.e., they have MPD. Our data are in parallel with the previous results of Sharifi and Pouresmael (2006) and Banyal and Sharma (2020), who reported MPD for B. persicum seeds, but different from those of Sharma and Sharma (2010) and Saeidnejad et al (2013), who reported only PD. However, none of these four studies provided any information on the embryo growth prior to germination, and hence the seed dormancy class was only determined based on seed germination responses to cold stratification and GA 3 treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Bonyanpour and Khosh‐khui (2001), Sharifi and Pouresmael (2006), Sasani et al (2007), Sharma and Sharma (2010), and Saeidnejad et al (2013) have reported that seed dormancy of B. persicum can be broken only by cold stratification; however, gibberellic acid (GA) alone breaks seed dormancy and increases germination rates (Amooaghaie & Ahmadi, 2017; Bahadori & Javanbakht, 2006; Emamipoor & Maziah, 2014; Kamali & Sadeghipour, 2016). In a previous study, germination of B. persicum seeds collected from India was promoted by GA, indole acetic acid, and kinetin at 4°C but not at 25°C; seed deterioration occurred at 25°C (Banyal & Sharma, 2020).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Three to four-year juvenile period is required to develop into Black Zira tuber and yield. The long life cycle of this plant prevents commercial cultivation of this plant (Banyal and Sharma 2020). Thus, the plant is critically endangered in natural habitats due to genetic erosion, pasture degradation, and early harvest.…”
Section: Introductionmentioning
confidence: 99%